2015
DOI: 10.1039/c5ob00356c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of multiply substituted 1,6-dihydropyridines through Cu(i)-catalyzed 6-endo cyclization

Abstract: Copper-catalyzed 6-endo cyclization of N-propargylic β-enaminocarbonyls was developed for the synthesis of oxidation-labile 1,6-dihydropyridines. This synthetic method allows flexible and regio-defined assembly of various substituents at the N1, C2, C3, C4, and C6 positions of 1,6-dihydropyridines under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…[22] If the N atom of N-propargyl enaminones is trisubstituted, 1,6-dihydropyridines can be also formed in the presence of a Cu(I)-catalyst (3-10 mol%). [23] Similar results were obtained in the presence of AgNO 3 (10 mol%). [24] Using CuCl 2 (20 mol%) and a base, N-propargyl enaminones cyclize into pyrroles.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…[22] If the N atom of N-propargyl enaminones is trisubstituted, 1,6-dihydropyridines can be also formed in the presence of a Cu(I)-catalyst (3-10 mol%). [23] Similar results were obtained in the presence of AgNO 3 (10 mol%). [24] Using CuCl 2 (20 mol%) and a base, N-propargyl enaminones cyclize into pyrroles.…”
supporting
confidence: 72%
“…Cyclization/aromatization has been achieved using stoichiometric amounts of CuI, as the oxidation of the cyclization products (dihydropyridines) into pyridines is not catalytic, with Cu(I) being reduced into Cu(0) . If the N atom of N ‐propargyl enaminones is trisubstituted, 1,6‐dihydropyridines can be also formed in the presence of a Cu(I)‐catalyst (3–10 mol%) . Similar results were obtained in the presence of AgNO 3 (10 mol%) .…”
Section: Methodsmentioning
confidence: 75%
“…23 In a closely related investigation, the Oguri group found that Npropargylic b-enaminocarbonyls 46 were converted to the corresponding substituted 1,2-dihydropyridines 47, via 6-endo-dig cyclization using [Cu(Xantphos)(MeCN)]PF 6 as catalyst in DCM at room temperature (Scheme 21). 24 Recently, Wan and co-workers performed the iodocyclization of N-propargylic b-enaminoesters 48 with N-iodosuccinimide as electrophilic source and developed a route to obtain 3-iodo-1,2 dihydropyridines 49 in good yields (Scheme 22a). A plausible mechanism for these electrophilic cyclizations is shown in Scheme 22b, where intermediate A, generated by the attack of iodonium ion to the alkyne moiety, undergoes 6-endo-dig cyclization, and then deprotonation, to afford 3-iodo-1,2dihydropyridine product 49.…”
Section: Pyridinesmentioning
confidence: 99%
“…One limitation is that triynes containing an ynoate or an ynone subunit gave variable results; presumably because these electron deficient alkynes reacted prematurely with some of the more nucleophilic tertiary amines. 8 This could be mitigated by using ynoates and ynamides containing a bulky TBS group on the terminus of the conjugated alkyne (cf. 6b and 6f ).…”
mentioning
confidence: 99%
“…The tri- or tetrayne precursors 6 cyclize to produce the benzynes 7 with convenient half-lives of reaction of a few hours at temperatures ranging from 80–130 °C. One limitation is that triynes containing an ynoate or an ynone subunit gave variable results; presumably because these electron-deficient alkynes reacted prematurely with some of the more nucleophilic tertiary amines . This could be mitigated by using ynoates and ynamides containing a bulky TBS group on the terminus of the conjugated alkyne (cf.…”
mentioning
confidence: 99%